2013
DOI: 10.1111/1365-2745.12168
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific functional differentiation suggests local adaptation to long‐term climate change in a calcareous grassland

Abstract: Summary1. Populations of the common perennial herb Plantago lanceolata L. have been exposed to nearly two decades of summer drought at the Buxton Climate Change Experiment (BCCIL), a controlled manipulation of climate factors in a species-rich limestone grassland in northern England. 2. We used a common garden approach to test for evidence of selection for different suites of functional traits in P. lanceolata populations exposed to chronic summer drought and across a soil depth gradient. 3. The main axis of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 69 publications
(94 reference statements)
2
36
0
Order By: Relevance
“…Specifically, we found that both vegetation and seed bank showed no response to supplemental summer rainfall. In response to drought, the previously reported significant reduction in drought-sensitive species associated with moist soils 26,29 was mirrored in the seed bank, although the effect of drought was greater on seed banks than on above-ground vegetation; 25,26 species of moist soils, such as C. panicea and P. erecta, simply disappeared from the seed bank after 14 years of drought. In contrast, C. rotundifolia and H. pulchrum, species whose seed banks showed significant responses to drought, did not show any responses above-ground in a previous analysis of ours.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Specifically, we found that both vegetation and seed bank showed no response to supplemental summer rainfall. In response to drought, the previously reported significant reduction in drought-sensitive species associated with moist soils 26,29 was mirrored in the seed bank, although the effect of drought was greater on seed banks than on above-ground vegetation; 25,26 species of moist soils, such as C. panicea and P. erecta, simply disappeared from the seed bank after 14 years of drought. In contrast, C. rotundifolia and H. pulchrum, species whose seed banks showed significant responses to drought, did not show any responses above-ground in a previous analysis of ours.…”
Section: Discussionmentioning
confidence: 88%
“…26 Sometimes, the response of the soil seed bank to climate variables may simply reflect the responses of the vegetation. In this case, the NMDS ordination suggests that compositional changes, at the community level, involving drought-resistant and sensitive species, species characteristic of wetter sites, 26 and perhaps even the local genetic differentiation recorded in some species above-ground 25 might be mirrored in the seed bank. Specifically, we found that both vegetation and seed bank showed no response to supplemental summer rainfall.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Studies on invasive plant species and biodiversity manipulation experiments show potential for fast local adaptation to abiotic and biotic components of the ecosystem (Callaway et al ., ; Lankau, ; Ravenscroft et al ., ; Zuppinger‐Dingley et al ., ). Our study shows a similar pattern in natural grassland systems, where variability in species composition of immediate neighbours results in an enhanced ability to modify morphology in response to neighbour identity.…”
Section: Discussionmentioning
confidence: 99%
“…to face climate change in situ (e.g. Davis & Shaw 2001;Malcolm et al 2002;Thomas et al 2004;Loarie et al 2009;Bullock et al 2012;Ravenscroft, Fridley & Grime 2014).…”
mentioning
confidence: 99%